2013
DOI: 10.1080/13825585.2012.665021
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for emotional faces in amnestic mild cognitive impairment: An event-related potential study

Abstract: This study examined the temporal course of emotional face recognition in amnestic mild cognitive impairment (aMCI). Patients and healthy controls (HC) performed a face recognition task, giving old/new responses to previously studied and novel faces displaying a negative or neutral expression. In aMCI patients, recognition accuracy was preserved for negative faces. Event-related potentials (ERPs) revealed disease-related changes in early perceptual components but not in ERP indices of explicit recognition. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 109 publications
2
32
2
Order By: Relevance
“…Similarly, visual EEF was not found in AD patients [26,70,71], either in intentional or incidental encoding [72], while mixed findings are reported in MCI subjects. Some indicate the absence of EEF for both positive and negative facial expressions [22,73] but other studies found that EEF for angry facial expressions or emotionally positive scenes is spared [26,29]. A limitation of these studies is that they tested emotional recognition in only one category of stimuli and by means of short/long term memory paradigms, i.e.…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, visual EEF was not found in AD patients [26,70,71], either in intentional or incidental encoding [72], while mixed findings are reported in MCI subjects. Some indicate the absence of EEF for both positive and negative facial expressions [22,73] but other studies found that EEF for angry facial expressions or emotionally positive scenes is spared [26,29]. A limitation of these studies is that they tested emotional recognition in only one category of stimuli and by means of short/long term memory paradigms, i.e.…”
Section: The Visual Discrimination Of Emotion In MCImentioning
confidence: 93%
“…Since MCI mainly affects the medial temporal and frontal structures normally involved in encoding emotional stimuli, a reduction in EEF would be expected. Nevertheless, neuroanatomical [25,26] and behavioural findings are still controversial [22,[27][28][29][30], possibly due to the different methodologies employed.…”
Section: Introductionmentioning
confidence: 97%
“…was significantly impaired on a YN test for object pictures but performed at normal levels on a 4-alternative FCC test (Holdstock et al, 2002). This dissociation has been replicated in two groups of amnestic Mild Cognitive Impairment (aMCI) patients (Westerberg et al, 2013; Westerberg et al, 2006), a group for whom there is growing evidence of impaired recollection and preserved familiarity, at least for visual stimuli (Anderson et al, 2008; Belleville, Ménard, & Lepage, 2011; Deason, Hussey, Budson, & Ally, 2012; Embree, Budson, & Ally, 2012; Hudon, Belleville, & Gauthier, 2009; O’Connor & Ally, 2010; Schefter et al, 2013; Serra et al, 2010). …”
mentioning
confidence: 91%
“…For example, the ERP P2, N2, and P3 components are recognized as effective electrophysiological indices in the early stage of MCI diagnosis [20][21][22][23], as MCI subjects have prolonged P2, N2, and P3 latencies, and reduced P3 amplitudes, compared to healthy elderly controls [20,[24][25][26]. Even specific to the MCI subgroups [e.g., amnestic MCI (aMCI)], these ERP components may also be useful for observing the differences in cognitive processes from those of the healthy elderly [20,24,27,28], and to distinguish the different MCI subtypes (e.g., aMCI versus nonaMCI) [29]. ERP components may thus be sensitive enough to identify elderly patients with early cognitive decline or disease progression to MCI and/or AD.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports over the past decade described the potential diagnostic importance of electrophysiological markers of cognitive decline in patients with MCI and the preclinical stage of AD, as obtained by analysis of the electroencephalography-derived event-related potentials (ERPs) [20][21][22][23][24][25][26][27][28][29]. For example, the ERP P2, N2, and P3 components are recognized as effective electrophysiological indices in the early stage of MCI diagnosis [20][21][22][23], as MCI subjects have prolonged P2, N2, and P3 latencies, and reduced P3 amplitudes, compared to healthy elderly controls [20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%